Psychology 2010 : the psychology of human development. Lecture 16. Developing language skills - Memorial University of Newfoundland. Educational Television Centre; Peterson, Carole, 1942-; Strawbridge, Jack (Memorial University of Newfoundland. Educational Television Centre, 1982)
Dr. Carole Peterson and Dr. Jack Strawbridge continue their discussion of language development in children. It includes screening an episode of The Growing Years (Coast Community College District, 1977) entitled "Developing Language Skills." This is followed by an interview with Dr. Harold Paddock of Memorial University who discusses dialect differences in Newfoundland. Joint instructors: Dr. Carole Peterson and Dr. Jack Strawbridge. Missing lectures 8-11. Minor distortion throughout.